2015
DOI: 10.3389/fphar.2015.00176
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Japanese herbal medicines for treatment of odontopathy

Abstract: This article highlights several refractory oral diseases, such as stomatitis, burning mouth syndrome (BMS), glossalgia, atypical facial pain (AFP), oral cancer, dry mouth, and Sjögren's syndrome (SJS), in which use of Japanese herbal medicines, Kampo medicines (KM), on the basis of Kampo theory could exert the maximum effects on human body. (1) In acute stomatitis, heat because of agitated vital energy may affect the head, chest, and middle abdominal region. Stomatitis is also related to the generation of reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 41 publications
(96 reference statements)
1
24
0
Order By: Relevance
“…Kamishoyosan (KSS, Chinese name: Jiaweixiaoyaosan, Korean name: Gamisoyosan) is a complex drug composed of 10 herbs. It is prescribed for climacteric disorder, dysmenorrhea, neurosis, and in cancer supportive therapy [18,19]. Hormones and cytokines released from adipocytes are involved in the aggravation of diseases for which KSS is prescribed [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Kamishoyosan (KSS, Chinese name: Jiaweixiaoyaosan, Korean name: Gamisoyosan) is a complex drug composed of 10 herbs. It is prescribed for climacteric disorder, dysmenorrhea, neurosis, and in cancer supportive therapy [18,19]. Hormones and cytokines released from adipocytes are involved in the aggravation of diseases for which KSS is prescribed [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“… 7 YKS has been administered to patients who show symptoms such as emotional irritability, neurosis, and insomnia and to infants who suffer from night crying and convulsions 8 . However, YKS has also recently been reported to be effective against pain disorders, such as headache, post-herpetic neuralgia, fibromyalgia, and trigeminal neuralgia 9, 10. Previous studies have demonstrated the antinociceptive effects of YKS in mice models with visceral pain 11 and rat models with chronic constriction injury 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Although the etiopathogenesis of intractable stomatitis has not been established, some type of immune-mediated pathogenesis and pathological roles of Reactive Oxygen Species (ROS) have been considered [4][5][6]9,10] . It is not known how KMs act against intractable stomatitis, but many KMs have anti-inflammatory and antioxidant activity that may be involved in this action [8,10,11] . Inchinkoto contains the following herbal extracts: Artemisia capillaris flower, gardenia fruit, and rhubarb.…”
Section: Etiopathogenesis Of Intractable Stomatitis and The Action Mementioning
confidence: 99%
“…Orento contains the following herbal extracts: pinellia tuber, coptis rhizome, processed ginger, glycyrrhiza, jujube, ginseng, and cinnamon bark. Coptis rhizome, glycyrrhiza, scutellaria root, and cinnamon bark have anti-inflammatory activity [10,13,26,27] . More specifically, cinnamon bark blocks the activation of the Mitogen-Activated Protein Kinases (MAPKs) known as Extracellular-Signal-Regulated Kinases (ERKs), cJun NH2-terminal kinases (JNKs), and p38 MAPKs [28] , and the use of cinnamon bark resulted in a reduction of TNF-α expression [28] .…”
Section: Etiopathogenesis Of Intractable Stomatitis and The Action Mementioning
confidence: 99%